Exploring Students' Perception on Learning Pronunciation through Podcast-Assisted in EFL Classroom - Sunita Aprilia Dewi; Yousef Bani Ahmad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
In this millenial era, the use of learning media as a crucial things to use for gain the students ability based on the learning goals. Podcast is one of the helper tools in English language skills, especially to increasing students’ pronunciation in EFL classroom because of the audio provide a speech of English Native Speaker. Pronunciation is the part of speaking ability which to master by the other people for make a good relation with another person in around the world, because of English is the unifier language. A narrative inquiry design was conducted for obtain the data, observation with interview are necessary. Three students in differents cognitive categories are participated in this researchat one of the Islamic High School in Karawang. Further podcast-assisted learning give the better atmosphere for the students in EFL class, also including motivation factor. As the conclusion all of the students perceive that podcast media is the preeminent and engrossment tools for learning pronunciation.